Open Loop Split Ring Resonator Based Thin Layer Dielectric Sensor - Naeem, Nadeem; Parveen, Sajida (Recent Advances in Electrical & Electronic Engineering, 2017)
Background: Split ring resonators are fundamental structures used to design metamaterial structures. These split ring resonators are designed for various scientific applications with complex and simple geometrical shapes. Metamaterials provide the extended spectral resolution, which is beyond the scope of conventional devices reported in open literature. Such metamaterials when operated on the non-ionizing terahertz frequencies (0.1-10 THz) are highly suitable for non destructive sensing of living organisms. Methods: The objective of this research work is to evaluate the performance of classic square split ring resonator as a metamaterial biosensor operating at terahertz frequency by depositing thin layers of dielectric materials resembled as hybridized layers of DNA sample. Results: Highly localized surface electric field distribution indicates strong LC resonance at resonant frequency. Electric field is focused on the capacitive coupled split gap area. The effective parameters of biosensor clearly showed left handedness that is negative permittivity and permeability and refractive index. Biosensor was analyzed by observing shift in transmission (S21) coefficients. Resonant frequency shifts itself towards the lower end of terahertz band due to the loading of thin layers of samples that are composed of different dielectric materials. Conclusion: Metamaterial biosensor sense the presence of tiny layers of different dielectric materials. This was due to the fact that disturbances in the surface electric field caused change in transmission of sensor's resonant frequency. The simple design of the sensor would overcome the issue of reusability of circuit. Such sensor would highly be suitable for sensing the presence of tiny bio molecules.
Keywords: dielectric layers